Preparation and characterization of single-hole macroporous organogel particles of high toughness and superfast responsivity - Tuncaboylu, Deniz C.; Okay, Oguz (Elsevier BV, 2009)
Abstract Crosslinked macroporous polymer particles containing a single large hole in their surfaces were prepared by solution crosslinking of butyl rubber (PIB) in benzene using sulfur monochloride (S2Cl2) as a crosslinking agent. The reactions were carried out within the droplets of frozen solutions of PIB and S2Cl2 at −18 °C. Spherical millimeter-sized organogel beads with a polydispersity of less than 10% were obtained. The particles display a two phase morphology indicating that both cryogelation and reaction-induced phase separation mechanisms are operative during the formation of the porous structures. The beads exhibit moduli of elasticity of 1–4 kPa, much larger than the moduli of conventional nonporous organogel beads formed at 20 °C. The gel particles also exhibit fast responsivity against the external stimulus (solvent change) due to their large pore volumes (4–7 ml/g). The gel beads prepared at −18 °C are very tough and can be compressed up to about 100% strain during which almost all the solvent content of the particles is released without any crack development. The sorption–squeezing cycles of the beads show that they can be used in separation processes in which the separated compounds can easily be recovered by compression of the beads under a piston.